Building a vision for more effective equity indices and planning tools - Rosan, Christina D.; Heckert, Megan; Zerbo, Russell; Benitez Mercado, Erykah (Frontiers in Sustainable Cities, 2022)
Recent years have seen a proliferation of equity indices and environmental justice screening tools to support more just environmental planning processes that attempt to quantify the concept of equity. While the equity index framework has proven important to advance the conversation around environmental equity and connect need to investments, we are concerned that these tools do not adequately address the intersectional nature of environmental justice concerns, effectively incorporate local knowledge on the lived experience of residents, or provide an actionable set of next steps to be taken. We see opportunities to rethink and expand on the equity index model to address issues of climate justice and preparedness through the development of Planning for Resilience and Equity through Accessible Community Technology (PREACT), a multipurpose and multi-scalar climate preparedness and neighborhood planning software application informed by both community need and community assets. This perspective article will discuss the theoretical and practical importance of adding these perspectives into screening tools and will describe our research in Philadelphia, PA aimed at understanding these challenges and developing a more inclusive and community-responsive methodology for effective tool development.